Mechanosensitive Piezo1 and Piezo2 ion channels in craniofacial development and dentistry: Recent advances and prospects - Lin, Yifan; Ren, Jianhan; McGrath, Colman (Frontiers in Physiology, 2022)
Mechanical forces play important roles in many biological processes and there is increasing interest and understanding of these roles. Mechanotransduction is the process by which mechanical stimuli are converted to biochemical signals through specific mechanisms, and this results in the activation of downstream signaling pathways with specific effects on cell behaviors. This review systematically summarizes the current understanding of the mechanosensitive Piezo1 and Piezo2 ion channels in craniofacial bone, tooth, and periodontal tissue, presenting the latest relevant evidence with implications for potential treatments and managements of dental and orofacial diseases and deformities. The mechanosensitive ion channels Piezo1 and Piezo2 are widely expressed in various cells and tissues and have essential functions in mechanosensation and mechanotransduction. These channels play an active role in many physiological and pathological processes, such as growth and development, mechano-stimulated bone homeostasis and the mediation of inflammatory responses. Emerging evidence indicates the expression of Piezo1 and Piezo2 in bone, dental tissues and dental tissue-derived stem cells and suggests that they function in dental sensation transduction, dentin mineralization and periodontal bone remodeling and modulate orthodontic tooth movement.